Analysis of Factors Associated with Non-Compliance Use of Personal Protective Equipment for Cleaning Staff at the Oku District Environmental Service - Lilia, Deli; Resta Agustin (Media Informasi, 2025)
Processing and handling of waste does not only end at the place or waste bin, but more than that, if the place or bin is full. Personal Protective Equipment (PPE) is a device used by officers to protect themselves from potential dangers and work accidents that may occur in the workplace. In 2023, according to the ILO, world figures say that every year there are more than 250 million workplace accidents and more than 160 million workers become ill due to workplace hazards. In Indonesia, work accidents in 2023 will amount to 370,747 cases. In South Sumatra Province the number of work-related accidents that occurred in 2023 was 6,665 cases, while in East OKU in 2023 there were 23 cases. This research aims to analyze factors related to non-compliance with the use of personal protective equipment in the OKU Regency Environmental Service. The research design in this study is to use quantitative with a cross-sectional approach. The research sample was Cleaning Officers at the OKU Regency Environmental Service, totaling 106 respondents. Data analysis used in the research is a statistical test using the Chi Square test. Based on the research results, it was found that the relationship between knowledge and non-compliance with the use of PPE was p value 0.000, the relationship between supervision and non-compliance with the use of PPE was p value 0.000, the relationship between work experience and non-compliance with the use of PPE was p value 0.000, the relationship between action and non-compliance with the use of PPE was p value 0.000. There is a relationship between the factors of knowledge, supervision, length of service and actions with non-compliance with the use of personal protective equipment at the OKU Regency Environmental Service